Intuition According to Imam al-Ghazali and It’s Role as Methods of Acquiring Knowledge - Hasib, Kholili; Zarkasyi, Amal Fathullah; Muslih, Muhammad Khalid (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
This article is aimed at elaborating on the role of intuition as a valid methodology in acquiring knowledge according to Imam al-Ghazali's thought. The concept of knowledge according to Imam al-Ghazali culminates in the thought of the Sufis. That is to make intuitive knowledge a very important knowledge than other knowledge. This study uses descriptive and philosophical analysis methods by using the philosophy of science of Prof. Syed M Naquib al-Attas. From the study conducted, it is known that Imam al-Ghazali mentions several terms for intuitive knowledge: ilham, mukasyafah, hads, or wijdan. However, the term mukasyafah was discussed more by Imam al-Ghazali in his work. Ilham and hads are sometimes referred to the same meaning. Mukasyafah is mentioned more because it seems that in Imam al-Ghazali's view it is the highest spiritual knowledge. Intuition through mukasyafah is included in the ma'rifah category. Imam al-Ghazali distinguishes between al-ilm and al-ma'rifah. Al-Ilm is knowledge acquired through reason and sensory experience. While ma'rifah is knowledge obtained through the method of intuition that culminates in the introduction to Allah SWT. However, from the study it was also found that between al-ilm and al-ma'rifah did not differ dichotomously. However, Imam al-Ghazali's view shows that al-ma'rifah must be the basis of the development of al-ilm. The purpose of acquiring knowledge through al-ilm must culminate in the introduction of Allah SWT. The acquisition of al-ilm is called al-mi'raj al-awwal (the first ladder of acquiring knowledge). The acquisition of al-ma'rifah is called al-mi'raj ats-tsaniyah (second ladder of acquiring knowledge). In al-mi'raj ats-tasniyah, one gets an understanding of the nature of reality and the real truth. With this basis, spiritual knowledge is the basis of all knowledge. So, scientists should not stop at acquiring knowledge in the alamu ash- shahadah but they need to improve their findings in the alam al-Malakut. If so, then scientists who use intuition as the basis of their knowledge, see the existence of nature that must be based on tauhid, namely the tauhid of the muqarrabun. The highest level of tauhid. So that someone can gain knowledge of wisdom and recognize the nature of this natural reality, namely the Absolute Reality of Allah SWT. Subsequently, a scientist can gain knowledge of wisdom (hikmah). This wisdom moves to do justice to nature. This perspective with high spirituality awareness gives birth to a fair attitude towards nature and the environment. Nature is not seen as an inanimate object that stands free, but nature is a manifestation of Allah SWT. In that way, he recognizes adab to nature.